Fpr3 and Zip3 Ensure that Initiation of Meiotic Recombination Precedes Chromosome Synapsis in Budding Yeast - MacQueen, Amy J. (2009)
BACKGROUND: Homolog pairing, synaptonemal complex (SC) assembly (chromosome synapsis), and crossover recombination are essential for successful meiotic chromosome segregation. A distinguishing feature of meiosis in budding yeast and mammals is that synapsis between homologs depends upon recombination; however, the molecular basis for this contingency is not understood. RESULTS: We show that the yeast proline isomerase, Fpr3, and the SUMO ligase, Zip3, ensure that SC assembly is dependent upon recombination initiation. When Fpr3 and Zip3 are absent, synapsis occurs even in a mutant that fails to initiate recombination and homolog pairing. Fpr3 and Zip3 appear to specifically prevent synapsis initiation at centromeric sites. This result is consistent with previous observations of SC proteins localizing to centromeres prior to and independent of meiotic recombination initiation. Finally, we show that without Fpr3 and Zip3 activities, the synapsis initiation components, Zip2 and Zip4, are dispensable for chromosome synapsis. CONCLUSION: Fpr3 and Zip3 represent parallel pathways that function, in a checkpoint-like manner, to ensure that chromosome synapsis is contingent on the initiation of recombination. We propose that, during normal meiosis, Zip2 and Zip4 act downstream of recombination signals to oppose Fpr3- and Zip3-mediated inhibitions to initiating SC assembly at centromeres. These data suggest a role for centromeres in coordinating major meiotic chromosomal events and draw an interesting parallel between yeast centromeres and C. elegans Pairing Centers.